Difference in dry matter accumulation with variable rates of sulphur and potassium application under calcareous soils in Brassica napus vs. B. juncea (Journal of Oilseed Brassica, 2026)
Improper sulphur (S) and potassium (K) fertilizer management decrease dry mater (DM) accumulation and yield in Brassica under calcareous soils. A field experiment was conducted at The University of Agriculture, Peshawar, Pakistan. The main objective of this study was to evaluate the effect of S and K fertilization on DM accumulation of Brassica species under calcareous soil at the study area. The experiment was conducted in a randomized complete block design using three replications. Each replication consisted of 20 treatments having two Brassica species [rape (B. napus) and Indian mustard (B. juncea)], three rates of S (15, 30, and 45 kg ha-1), three rates of K (30, 60, and 90 kg ha-1) and one control (no S and K applied). The DM accumulation at various growth stages increased with K and S fertilization as compared to the zero-S/ zero-K control plots. Both species responded positively to K and S fertilization, but the magnitude of response varied with levels of S and K. It was concluded that a combination of 60 kg K + 30 kg S ha-1 could improve DM accumulation and yield in Brassica species.